POLYPHARMACY AND USE OF POTENTIALLY INAPPROPRIATE MEDICATIONS IN PATIENTS WITH DEMENTIA AND MILD COGNITIVE IMPAIRMENT - Dhikav, Vikas; Sethi, Mansi; Singhal, Arjun Kumar; Anand, Ks (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Polypharmacy and the use of potentially inappropriate medications (PIM) are common among the elderly worldwide, but there is a paucity of data in patients with dementia in this regard. This study was aimed at assessing the average number of drugs being taken by the elderly patients with dementia presenting to our clinic and whether their prescriptions included the Potentially Inappropriate Medications (PIM) or not. Methods: In our study we recruited patients who presented to the Outpatient Department of Neurology. The use of PIM was estimated according to the Beer's Criteria. Polypharmacy was defined as the consumption of 5 or more drugs. Results: We incorporated 143 patients in our study where the ratio of Males: females were 110:33. The mean age of our patients was 70.1 ± 10.1 years. Out of all the patients recruited, 55 had mild cognitive impairment, 45 patients had Alzheimer's disease, 30 had vascular dementia and a minority had fronto-temporal dementia (3), progressive primary aphasia (7) and dementia with Lewy bodies (3). Out of the 143 patients of dementia in our study, 60 patients were taking drugs having the potential to cause cognitive impairment. Distribution of these drugs was as follows: beta blockers (by 10 patients), trihexyphenidyl (THP) (by 3 patients), carbamazepine (2), olanzapine (7), tolterodine (3), oxybutynin (2), amytriptaline (3), loperamide (2), zolpidem (25) and alprazolam (3). According to our study majority of the medications having the potential to cause cognitive impairment were prescribed by psychiatrists (27 patients), followed by physicians (23 patients) and Neurologists (10 patients). Among the 25 patients taking Zolpidem, 18 were taking 10mg per day while 7 were taking 5mg per day. A total of 86 patients were receiving other medications like multi-vitamins (55), calcium (20) and vitamin D (11). Lastly the average number of drugs being consumed by elderly patients with dementia was 8.24±3.2. Conclusion: Drugs having the potential to cause cognitive impairment were being prescribed to patients already suffering from dementia or mild cognitive impairment. A number of patients are consuming multivitamins and many a times these are prescribed without assessing whether they are actually needed in the patient or not. Also the prevalence of polypharmacy in Indian prescriptions is evident according to our study. Keywords: Alzheimer's disease, polypharmacy, potentially inappropriate medications, cognitive impairment, dementias, mild cognitive impairments, elderly.